2023
DOI: 10.1021/acs.jpca.3c02834
|View full text |Cite
|
Sign up to set email alerts
|

Linear Scaling Calculations of Excitation Energies with Active-Space Particle–Particle Random-Phase Approximation

Jiachen Li,
Jincheng Yu,
Zehua Chen
et al.

Abstract: We developed an efficient active-space particle− particle random-phase approximation (ppRPA) approach to calculate accurate charge-neutral excitation energies of molecular systems. The active-space ppRPA approach constrains both indexes in particle and hole pairs in the ppRPA matrix, which only selects frontier orbitals with dominant contributions to low-lying excitation energies. It employs the truncation in both orbital indexes in the particle− particle and the hole−hole spaces. The resulting matrix, whose e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 97 publications
1
13
0
Order By: Relevance
“…It has been shown that using an active space of only 30 occupied and 30 virtual orbitals, active-space ppRPA achieves fast convergence to within 0.05 eV compared to full ppRPA for molecular excitations of different characters, including charge transfer, Rydberg, double, and valence excitations as well as diradicals. 54 As a result, the ppRPA calculations for molecular excitations become linear scaling and are more efficient than the ground-state SCF calculations of the same molecules.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that using an active space of only 30 occupied and 30 virtual orbitals, active-space ppRPA achieves fast convergence to within 0.05 eV compared to full ppRPA for molecular excitations of different characters, including charge transfer, Rydberg, double, and valence excitations as well as diradicals. 54 As a result, the ppRPA calculations for molecular excitations become linear scaling and are more efficient than the ground-state SCF calculations of the same molecules.…”
mentioning
confidence: 99%
“…Thus, we choose to use the active space composed of 200 occupied and 200 virtual orbitals in all ppRPA calculations in this work. Compared with the previous work of using the active-space ppRPA approach for molecular systems, 54 the number of orbitals needed in the Figure 1. Vertical excitation energies of NV − in diamond obtained from ppRPA@PBE with respect to the number of orbitals in the active space.…”
mentioning
confidence: 99%
See 3 more Smart Citations